SUPLEMENTACIÓN DE CÁSCARA DE CACAO (Theobroma cacao L.) EN VACAS MESTIZAS LECHERAS EN PASTOREO EN LA GANADERÍA BOVINA DE LA FCPB 2022 - Bautista Alvarado, Jordy Anthony (2023)
The present work was carried out in the FCPB Bovine Program, with the objective of evaluating cocoa shell in the diet of grazing cross-breed dairy cows, using a Latin square design with percentages of cocoa shell plus grazing (1% MSCDC + grazing; 1.5% MSCDC + grazing; 2% MSCDC + grazing; 2.5% MSCDC + grazing and 100% grazing). The variables evaluated were bromatological analysis of Savoy grass and cocoa shell, feed consumption, chemical composition and milk production.